2014
DOI: 10.1007/s00520-014-2129-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention strategies for chemotherapy-induced hand–foot syndrome: a systematic review and meta-analysis of prospective randomised trials

Abstract: From all available possibilities for the prevention of HFS, celecoxib appears to be the most promising, with statistically significant results. Larger, multicentric studies are required to reinforce this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 37 publications
1
68
0
13
Order By: Relevance
“…It may appear that numerous clinical trials have been performed, but in fact, the majority of them have limited value (5). Preventive approaches for PPE, including administration of moisturizers, regional cooling of the skin, and avoidance of excessive activities associated with overheating or trauma, have been evaluated in non-randomized trials (4,16). The use of topical antiperspirant with a beneficial effect has also been reported in the literature (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may appear that numerous clinical trials have been performed, but in fact, the majority of them have limited value (5). Preventive approaches for PPE, including administration of moisturizers, regional cooling of the skin, and avoidance of excessive activities associated with overheating or trauma, have been evaluated in non-randomized trials (4,16). The use of topical antiperspirant with a beneficial effect has also been reported in the literature (17).…”
Section: Discussionmentioning
confidence: 99%
“…Pyridoxine appeared to be a promising agent for the prevention of PPE, but in randomized controlled trials, it proved to be ineffective (18,19). In a meta-analysis conducted by Macedo et al (16), celecoxib exclusively demonstrated a 53% risk reduction (odds ratio, 0.47; 95% confidence interval, 0.29-0.78; P= 0.003) of any grade PPE. Certain studies have indicated that dimethyl sulfoxide (20) or corticosteroids (21,22) may be beneficial in the treatment of PLD-induced dermal complications, as they accelerate skin recovery, but in fact, the only well-established preventive management includes dose intensity modification or complete chemotherapy discontinuation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic prophylactic treatments consist of oral pyridoxine, oral celecoxib, corticosteroid/H 2 blockers, vitamin E, and oral cod liver oil [85][86][87][88][89][90][91][92][93][94]. A recent meta-analysis by Macedo et al [95] revealed that, of the available topical and pharmacologic prophylactic measures, celecoxib appears to be the only promising agent for the prevention of HFS with statistically significant results. In terms of preventive measures for MKI-induced HFSR, no previous trial has systematically tested the effectiveness of pharmacologic treatment.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…A larger, multicenter, double blind trial is necessary; however, to confirm this hypothesis. 10 Topical adapalene when applied for 3 months significantly reduced the inflammation and pain following chemotherapy. Topical retinoids may have the potential to effectively treat capecitabine induced HFS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the advent of new drugs such as multikinase inhibitors in this era of targeted therapy, the presence of HFS shall remain a limiting factor for more years to come. 10 Prevention of HFS would be imperative to avoid treatment delays and interruptions. Celecoxib appears to be the most promising agent for the prevention of HFS.…”
Section: Discussionmentioning
confidence: 99%